The index of microcirculatory resistance measured acutely predicts infarct severity and left ventricular function at 3 months in patients with ST segment elevation myocardial infarction. (22nd September 2015) - McGeoch, RJ; Watkins, S; Berry, C; Davie, A; Byrne, J; Hillis, WS; Robb, SD; Lindsay, MM; Dargie, HJ; Oldroyd, KG
Abstract : Background: Contrast enhanced cardiac magnetic resonance imaging (ceCMR) is the gold standard for the assessment of microvascular obstruction (MVO), left ventricular ejection fraction (LVEF) and infarct volumes in patients with ST elevation myocardial infarction (STEMI). However, ceCMR is not available acutely. The index of microcirculatory resistance (IMR) is a simple novel invasive measure of microvascular function that can be measured at the time of emergency percutaneous coronary intervention (PCI). We investigated the relationships between IMR, MVO and other measures of myocardial injury in STEMI. Methods: Fifty-seven STEMI patients who gave informed consent were included. Using a coronary pressure/temperature-sensitive guidewire in the culprit artery, mean coronary transit times (Tmn ) were obtained following bolus intracoronary injection of 3 ml saline at the end of the PCI procedure. As IMR may be affected by the microsenor position, the distance of the microsensor from the ostium of the instrumented artery was standardised to 6–9 cm. Tmn and distal coronary pressure (Pd ) were obtained under conditions of peak hyperaemia achieved by intravenous adenosine infusion (140 μg/kg per minute). IMR was calculated as Pd × Tmn . Patients underwent baseline ceCMR 24–48 h later and at 3 months follow-up. Left ventricular dimensions were assessed using retrogated (trueFISP) cinematographic breath hold sequences and MVO was defined as a dark core of hypoenhancement within the area of hyperenhanced infarcted tissue using breath hold turboFLASH sequences 15 minutes after an intravenous bolus of gadolinium (0.1 mmol/kg). Results: Physiological measurements were successfully achieved in all consenting patients, 52 patients had complete baseline ceCMR scans and 47 complete follow-up scans. The median IMR (interquartile range; IQR) was 34.8 (22.9–50.6) and the range was 9.9–186.3. Twenty seven patients (52%) had MVO. IMR (median (IQR)) was higher in patients with MVO (38.8 (30.2–56.2)) compared with in patients without MVO (26.8 (18.7–36.6)); p = 0.003). IMR predicted LVEF inversely at baseline (r 2  =  29.1%; p<0.001) and at follow-up (r 2  =  14.5; p = 0.007). IMR at the time of PCI also predicted the percentage infarct size at baseline (r 2  =  18.6%, p = 0.001) and at follow-up (r 2  =  15.6%, p = 0.006). Conclusions: The IMR measured acutely at the end of emergent PCI predicts infarct size and left ventricular function in the longer term. The prognostic utility of this technique in STEMI patients undergoing PCI merits further assessment.